Shoulder the sky - Perry, Anne. (New York : Ballantine Books, 2004)
Great Britain
1
Keywords: Journalists -- Fiction; World war, 1914-1918 -- Trench warfare -- Fiction; World War, 1914-1918 -- England -- Fiction; Reavley family (Fictitious characters) -- Fiction